Augmentation pharyngoplasty for treatment of velopharyngeal insufficiency in children: Results with injectable dextranomer and hyaluronic acid copolymer. (1st September 2016) - Cofer, Shelagh A.; Baas, Becky; Strand, Edythe; Cockerill, Cara C.
Abstract : Objectives/Hypothesis: To evaluate the effectiveness, durability, and safety of a tissue filler (dextranomer and hyaluronic acid copolymer) when injected submucosally in the nasopharynx to treat velopharyngeal insufficiency (VPI) in pediatric patients. Study Design: Retrospective case series. Methods: Charts were reviewed for all patients treated with injectable filler at a tertiary children's center for VPI from April 2010 through September 2013. Main outcome measures included perceptual speech assessments before and after the procedure, velopharyngeal gap size on nasendoscopy, and nasalance. Length of follow‐up, length of surgery, hospital admission, and complications were also identified. Results: After injection augmentation pharyngoplasty, 93% of patients had no or mild hypernasality, 83% had resolution of nasal grimace, and 96% had resolution of audible nasal emission. Complications were minor and included mucosal infection, neck pain, snoring, and obstructive sleep apnea. Conclusions: Use of injectable filler to augment the nasopharynx is an effective, minimally invasive therapy for small or moderate‐sized velopharyngeal gaps, with shorter procedural times, easier recovery, and acceptable durability. Level of Evidence: 4 Laryngoscope, 126:S5–S13, 2016